Biology of Ochrogaster lunifer Herrich-Schaeffer (Lepidoptera: Thaumetoedae), a defoliator of Acacia acuminata Bentham, in the Western Australian wheatbelt - Van Schagen, John; Majer, Jonathan; Hobbs, R. (1992)
Ochrogaster lunifer is a serious defoliator of Acacia acuminata in the Western Australian wheatbelt, and also of several other Acacia spp. across the southern half of Australia. This paper describes its life cycle in the south of Western Australia. It is univoltine with six larval instars occurring from January to June, and adults in November and December. Larvae are gregarious feeders and live together in a bag made of grass and cast skins covered with silk.